DARAH DAN KOPI DALAM RACIKAN MEDIA: Konstruksi Pemberitaan Kompas.com dan Metrotvnews.com Terkait Kasus ‘Kopi Sianida’ Jessica Wongso - Sari, Nursita (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
The mass media has the ability to construct realities that can represent a particular person or idea in its reporting. One of them is what the media did to Jessica Kumala Wongso, a suspect in the Wayan Mirna Salihin murder case using "cyanide coffee". Kompas.com and Metrotvnews.com are examples of online media that represent Jessica in their news. This study uses a qualitative approach to see how Kompas.com and Metrotvnews.com represent and construct the reality of Jessica. Using the Fairclough model's critical discourse analysis method, this study specifically examines how Jessica was constructed by the media and what contexts influenced it. The results of text analysis, document searches, and literature reviews show that Kompas.com and Metrotvnews.com represent Jessica as a murderer from the upper class who is cruel and has sexual abnormalities. Text analysis also identified gender discrimination that intersected with social class and sexual preference towards Jessica. This discrimination has led to violations of journalistic principles because of the attitude of the media that only pursues market interests. To cite this article (7th APA style): Sari, N. (2016). Darah dan Kopi dalam Racikan Media: Konstruksi Pemberitaan Kompas.com dan Metrotvnews.com Terkait Kasus ‘Kopi Sianida’ Jessica Wongso [How Kompas.com and Metrotvnews.com Contruct the News about Jessica Wongso’s ‘Cynide Coffee’]. Journal Communication Spectrum, 6(1), 1-14.